Ergonomic assessment of the surgeon's physical workload during standard and robotic assisted laparoscopic procedures. Issue 2 (26th March 2013) - Hubert, N; Gilles, M; Desbrosses, K; Meyer, JP; Felblinger, J; Hubert, J
Abstract Background Standard laparoscopy is responsible for musculoskeletal problems because of surgeons anti‐ergonomic positions. Robot‐assisted laparoscopy seems to reduce these musculoskeletal disorders thanks to the surgeons seated position. The objective of this study is to evaluate the muscular strain and cognitive stress induced by these two techniques during real operations conducted on the pig. Methods Electromyographic activities, heart rate, physical and mental workloads (NASA Tlx and Borg CR‐10) were recorded. Results Physical workload and perception of the effort invested was significantly greater during the standard laparoscopies (p<0.05). Mental stress was however identical for the two techniques. In Standard Laparoscopic group, greater physical activity was found for trapezius and dorso‐lumbar muscles, and significant appearance of fatigue of the trapezius muscles should also be noted. Finally, heart rate during standard laparoscopy was increased (92.1 ± 1.6 bpm vs 83.7 ± 1.8, p<0, 01), confirming greater physical expenditure. Conclusions Robot‐assisted laparoscopy is a less physically stressful surgical technique than standard laparoscopy. Copyright © 2013 John Wiley & Sons, Ltd.